2000
DOI: 10.14411/eje.2000.074
|View full text |Cite
|
Sign up to set email alerts
|

Influence of host plants on specialist / generalist aphids and on the development of Adalia bipunctata (Coleoptera: Coccinellidae)

Abstract: Abstract. The aim of this work was to determine the impact of allelochemicals (glucosinolates/isothiocyanates) from Brassicaceae (Brassica napus and Sinapis alba) at two trophic levels in relation to biological control efficacy. The impact of these plants on aphid Myzus persicae (Sulzer) and Brevicoryne brassicae (L.) and ladybird Adalia bipunctata (L.) biology can be assessed by observation of several developmental parameters: mortality, development duration and adult weight. Sub-lethal toxicity can also be m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
1
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 28 publications
5
29
1
2
Order By: Relevance
“…Thus, while in the study of Francis et al (2000) none of the ladybird larvae fed B. brassicae reared on S. alba reached the adult stage, 45% of syrphids did in the present study. The higher mortality rate of both predator species on a diet of B. brassicae reared on S. alba compared to those fed other diets suggests a transfer of the plant's secondary metabolites through the specialist aphid prey.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Thus, while in the study of Francis et al (2000) none of the ladybird larvae fed B. brassicae reared on S. alba reached the adult stage, 45% of syrphids did in the present study. The higher mortality rate of both predator species on a diet of B. brassicae reared on S. alba compared to those fed other diets suggests a transfer of the plant's secondary metabolites through the specialist aphid prey.…”
Section: Discussioncontrasting
confidence: 69%
“…Feeding on B. brassicae reared on S. alba resulted in higher larval predator mortality compared either to feeding on the aphid reared on its other host plant, B. napus, or feeding on another aphid species (M. persicae) reared on Brassica or on a GLS free plant. Francis et al (2000) previously demonstrated that toxicity of B. brassicae for A. bipunctata larvae increases with the increasing glucosinolate contents of the host plants. The present study reveals that the Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The efficacy of the aphid defence depends on the detoxification ability of its predator. The ladybird A. bipunctata is very sensitive to the isothiocyanates produced by the cabbage aphid Brevicoryne brassicae as its GSTs saturate quickly whereas the hoverfly E. balteatus GSTs allow it to feed on that prey 2000;Vanhaelen et al, 2001;2002).…”
Section: Discussionmentioning
confidence: 99%
“…The influence of plant allelochemicals is not limited to the herbivores; specialized phytophagous insects such as the lupin aphid, Macrosiphum albifrons Essig, can also use them as defence substances, which affect pest predator biology (10). High mortality rates were observed when the two-spot ladybird, Adalia bipunctata L., was fed with aphids reared on Brassicaceae species (11). Increasing GST activity was detected in surviving ladybirds and was correlated with increasing glucosinolate concentrations in the prey host plant (12).…”
Section: Introductionmentioning
confidence: 99%